Individual repeatability of foraging behaviour in a marine predator, the great cormorant, Phalacrocorax carbo. (May 2015) - Potier, Simon; Carpentier, Alexandre; Grémillet, David; Leroy, Boris; Lescroël, Amélie
Abstract : Intrapopulation variability, especially individual foraging specialization, has been investigated in many species. Nevertheless, the repeatability of foraging behaviour remains poorly understood. In particular, whether individuals differ in their respective degrees of repeatability still remains to be determined. Here, we estimated foraging behaviour repeatability in the great cormorant, at both the population and the individual levels, and assessed the effect of repeatability on individual foraging performance. At the population level, we found that some foraging variables were more repeatable (e.g. departure angle and trip duration) than others (e.g. time spent underwater per trip). At the individual level, we found differences in the degree of repeatability for each foraging variable, highlighting the presence of both highly flexible and highly consistent individuals in the population. The effect of repeatability on individual performance depended on the considered timescale: individual-level repeatability of time spent underwater per dive was negatively related to foraging efficiency while individual-level repeatability of time spent underwater per trip was positively related to foraging efficiency. Overall, our study demonstrates the importance of studying repeatability at the individual level and shows how both flexibility and consistency in animal behaviour shape their ability to extract energy from the environment. Highlights: Individual repeatability of foraging behaviour was estimated for great cormorants. Individuals differed in their degree of repeatability in foraging behaviour. Individual repeatability of specific behaviour influenced foraging efficiency. Repeatability was more variable between individuals than between sexes. Future studies should also consider behavioural repeatability at the individual level.